Preliminary study of nematode resistance to anthelmintic drugs in two goat farms in terengganu - Asmad, Kari; Faisal, Abubakar; Tijjani Haruna, Usman (Penerbit UTM Press, 2015)
Gastrointestinal nematodes considered to be among the factors that could affect the goats’ productivity. The objective of this study was to evaluate the current status of nematode resistance to anthelminthic drugs in two farms (Veterinary Research Academy Jenang, Marang and Hulu Seladang Setiu Farms). The goats were randomly divided into five treatments which include control (A), albendazole oral administration (B), levamisole oral administration (C), ivermectin subcutaneous injection (D) and ivermectin pour on groups (E). After two weeks of the treatment the feces were collected and fecal egg count was examined. The mean of fecal egg count reduction (FECR) obtained was not statistically (p>0.05) different between the treatments, and FECR% was lower than 66% in all of the five treatments (A, B, C, D and E). In conclusion, two farms revealed the resistance of nematode to Albendazole, Levamisole, and Ivermectin anthelmintic drugs. This study suggested that the anthelmintic treatment is unlikely to be the suitable method of controlling nematode population, thus studies are needed to investigate further on the effectiveness of other methods of control such as the use of herbs.